Analisis Penjaminan Mutu pada Pendidikan Sekolah Menengah Kejuruan: Sebuah Tinjauan Singkat - Novitanti; Ica Rahayu Situmorang (AGUSPATI RESEARCH INSTITUTA, 2023)
The purpose of writing this article is a Narrative Literature Review on the implementation of quality assurance in vocational schools, to describe the obstacles encountered in building a school management system to improve the quality of education services. considering that there is still a public opinion that the quality of education services is not optimal. The type of method used is a qualitative method. An apparently poor quality record will be corrected through continuous quality performance. Efforts to achieve quality planned by the school education quality assurance team, set forth in a quality implementation planning document, include the following steps: establishing quality standards, mapping quality, preparing quality compliance plans, conducting quality compliance, and assessing quality compliance.